Adolescent Perceptions of Educators with Physical Challenges - Marie Beattie (Educational Considerations, 2007)
In 1987, I had a massive stroke, possibly caused by a brain tumor. Before this, I had been a special education teacher for 13 years. The stroke caused me to have to relearn basic math, language, and motor functions.
Keywords: disability; challenges; educators; perceptions; adolescent; students